Grupo de funcionarios en una sala de reuniones.
Aparecen Álvaro Avilés Vargas, Nidia Lobo Solera, Marcelo Blanc Masías, Enrique Góngora Trejos, Francisco Antonio Pacheco Fernández, Sergio Flores Alvarez, Minor Vargas Calvo, en una reunión